Detectors and instruments for detection of X-ray radiation on the basis of zinc selenide crystals - Ryzhikov, V.D.; Volkov, V.G.; Opolonin, O.D.; Makhota, S.V.; Maksymchuk, V.V. (Functional Materials, 2015)
Theoretical analysis and experimental studies have been carried out of parameters of two-layer sandwich-detector of scintillator-photodiode type, in which the low-energy detector works both as absorption filter of low-energy fraction of radiation for the high-energy detector and detector of the low-energy radiation. The energy dependence deviation does not exceed ±5 % in the range from 30 to 120 keV. The developed detector and the instrument designed on its base allow contactless measurement of anode voltage of X-ray emitter from 40 to 140 kV with accuracy of ±3 %. The dose rate measurement range is 1-200 R/min.